2015
DOI: 10.1111/j.1439-0531.2009.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Programmes of Ovulation Synchronization in the Treatment of Ovarian Cysts in Dairy Cows

Abstract: It was the aim of this field study to evaluate two different protocols of ovulation synchronization for the treatment of ovarian cysts and their effect on reproductive performance in dairy cows. In addition, factors with a possible influence on treatment success and pregnancy outcome as well as costs per pregnancy were analysed. The study was performed with 130 German Holsteins with ovarian cysts diagnosed on days 55 to 60 postpartum. Cows belonging to group 1 (n = 65) received a modified ovsynch protocol [day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
(44 reference statements)
3
11
0
Order By: Relevance
“…The conception rates by timed AI of both protocols for the cystic ovarian diseases were around 45% in this study. These conception rates are higher than those in previous reports in which conventional Ovsynch was used (18.3% [11] and 23.1% [12]) and are almost equivalent to those in the previous reports in which CIDRbased timed AI protocols were used (52.3% [18] and 36.7% [19]). Conception rates in dairy cows could be affected by various factors including postpartum interval, parity and milk yield [24,25].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The conception rates by timed AI of both protocols for the cystic ovarian diseases were around 45% in this study. These conception rates are higher than those in previous reports in which conventional Ovsynch was used (18.3% [11] and 23.1% [12]) and are almost equivalent to those in the previous reports in which CIDRbased timed AI protocols were used (52.3% [18] and 36.7% [19]). Conception rates in dairy cows could be affected by various factors including postpartum interval, parity and milk yield [24,25].…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand, cows with luteinized cysts can be successfully treated with PGF2α when correctly diagnosed [1]. Recently, the Ovsynch protocol, which is an ovulationsynchronization protocol, or an estrus-synchronization protocol that uses a controlled internal drug releasing (CIDR) followed by PGF2α, has been applied to treat dairy cows with ovarian cysts in a few reports [11,12]. It has been suggested in postpartum suckled beef cows that the addition of a CIDR to the conventional Ovsynch protocol (Ovsynch plus CIDR) increases plasma progesterone concentrations on the day of PGF2α treatment, 7 days after the beginning of the Ovsynch, and induces a clear rise of estradiol-17β concentrations from the time of the PGF2α treatment to the time of the second GnRH treatment, and that it improves conception rates after timed AI [13][14][15][16][17].…”
mentioning
confidence: 99%
“…It has been suggested that, besides the clinical response, reproductive performance should be considered as treatment success, especially from the economic point of view (11). In our study, the best reproductive results were associated with GnRH/PGF2α treatment and took the form of a higher pregnancy rate (63%) than in the control group (54%) and a shorter calving-conception period than in GnRH and control groups.…”
Section: Discussionmentioning
confidence: 55%
“…It is well known that the spontaneous recovery percentage of cysts is relatively high (up to 60%), especially in earlier post partum stages (18). However, despite this phenomenon, the hormonal treatment of cysts is recommended, due to the better reproductive performance in treated cows (11,20,27).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors affect the incidence of ovarian cysts, including environmental factors, season, herd management, and the age, milk yield, body condition score and uterine diseases of the animal [11,42]. It was reported previously, incidence of luteal cysts ranges between 15.4% and 39.85% as well as it is between 60.1% and 84.6% in follicular cysts [19,26]. Contrary to the above mentioned studies, the incidence of luteal cysts (59.2%) was found to be higher than follicular cysts (40.8%) in the present study.…”
Section: Discussionmentioning
confidence: 99%